2017
DOI: 10.1007/s11248-017-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a novel bi-directional Brassica napus promoter in soybean

Abstract: The expression profile of a natural bi-directional promoter, derived from the Brassica napus EPSPS-A gene, was studied in transgenic soybean (Glycine max C.V. Maverick) lines. Two constructs, pDAB100331 and pDAB100333, were assembled to test the bi-directionality of the promoter. Two reporter genes, gfp and gusA, were employed and they were interchangeably placed in both constructs, one on each end of the promoter such that both proteins expressed divergently in each construct. In the T generation, GUS express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The reverse promoter mainly means that its forward promoter cannot drive the expression of foreign genes. However, a few studies are reported on plant reverse promoters, most of the studies are focused on bi-directional promoters, such as BEAP [ 23 ], Cab1/2 [ 24 ] and BDDP [ 25 ]. Rice is one of the most important food crops in the world [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reverse promoter mainly means that its forward promoter cannot drive the expression of foreign genes. However, a few studies are reported on plant reverse promoters, most of the studies are focused on bi-directional promoters, such as BEAP [ 23 ], Cab1/2 [ 24 ] and BDDP [ 25 ]. Rice is one of the most important food crops in the world [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soybean (Glycine max­[L.] Merr) seeds are very rich in protein (∼40%) and oil (∼20%) content. There is a renewed interest in research to increase the percent of seed proteins in soybean, especially for the food industries that depend on soybean protein as a major source of their raw materials. Genetic research with soybean has been augmented by the submission of the reference genome sequence in 2010, which greatly enhanced the scope of exploration of niches to improve soybean seed quality …”
Section: Introductionmentioning
confidence: 99%
“…In the present study the primary objective is to develop gene constructs for high level tissue specific expression of genes in pods of chickpea. Contextually, use of chimeric promoters or Bidirectional Duplex promoters (BDDP) in combination with strong terminators has been shown to drastically enhance transcriptional efficiency of genes (Chen et al, 2018, Chennareddy et al, 2017, Li et al, 2004. However, use of tissue specific promoters as BDDP in combination with transcriptional and translational enhancers has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%